Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.jmedchem.8b01085
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 3-Ethyl-4-(3-isopropyl-4-(4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl)benzamide (TAS-116) as a Potent, Selective, and Orally Available HSP90 Inhibitor

Abstract: The molecular chaperone heat shock protein 90 (HSP90) is a promising target for cancer therapy, as it assists in the stabilization of cancer-related proteins, promoting cancer cell growth, and survival. A novel series of HSP90 inhibitors were discovered by structure–activity relationship (SAR)-based optimization of an initial hit compound 11a having a 4-(4-(quinolin-3-yl)-1H-indol-1-yl)­benzamide structure. The pyrazolo­[3,4-b]­pyridine derivative, 16e (TAS-116), is a selective inhibitor of HSP90α and HSP90β a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 62 publications
(154 reference statements)
1
28
0
Order By: Relevance
“…Another set of indole derivatives with a similar substitution at position 1 of the indole skeleton was reported by Tamoo [ 181 ] and Uno ( Figure 9 ) [ 182 ]. On the basis of extensive SAR studies, it was found that F9-1 is an inhibitor of cPLA 2α (with an IC 50 value of 0.075 μM) [ 181 ], and indole F9-2 is a selective inhibitor of both HSP90 (IC 50 = 0.069 μM) and SK-Br-3 (IC 50 = 0.33 μM) [ 182 ]. The introduction of the aryl substituents was accomplished via copper-catalyzed Ullman condensation at reaction temperatures above 100 °C.…”
Section: N -Arylated Indoles As Biologically Active Substancessupporting
confidence: 53%
“…Another set of indole derivatives with a similar substitution at position 1 of the indole skeleton was reported by Tamoo [ 181 ] and Uno ( Figure 9 ) [ 182 ]. On the basis of extensive SAR studies, it was found that F9-1 is an inhibitor of cPLA 2α (with an IC 50 value of 0.075 μM) [ 181 ], and indole F9-2 is a selective inhibitor of both HSP90 (IC 50 = 0.069 μM) and SK-Br-3 (IC 50 = 0.33 μM) [ 182 ]. The introduction of the aryl substituents was accomplished via copper-catalyzed Ullman condensation at reaction temperatures above 100 °C.…”
Section: N -Arylated Indoles As Biologically Active Substancessupporting
confidence: 53%
“…This may be due to the pleiotropic effects of HSP90 inhibition. The effective concentrations of the HSP90 inhibitors in this assay were generally comparable to values for blocking the growth of cancer cells in culture ( 49 , 50 , 52 , 53 , 54 ), although there was variability of the potency of the compounds in blocking different tumor cells. Detailed statistical analysis was performed using GraphPad Prism software, and the P values calculated using the ANOVA Kruskal-Wallis multiple comparison test are shown in supplemental Fig.…”
Section: Resultsmentioning
confidence: 62%
“…For instance, the reported IC 50 for ganetespib is 5 nM ( 59 ), and we see the half maximal effect at 5 nM. For TAS-116, the reported value is 69 nM ( 53 ), and we see the half maximal effect near that dose.
Fig.
…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…While a number of HSP90 inhibitors are undergoing clinical trials, there are currently no approved anticancer drugs that act on this pathway, highlighting the need for further investigation of small molecules targeting HSPs (see References [ 172 , 173 ] for reviews focusing on the targeting of HSPs and HSP90, respectively). Uno et al reported a series of molecules based on preliminary hit 190 as potential HSP90 inhibitors [ 174 ]. Compound 190 was a hybrid compound designed from the X-ray crystal structures of two previous inhibitors of HSP90.…”
Section: Imidazoles As Inhibitors Of Other Targetsmentioning
confidence: 99%